The Effect of The Auditory, Intellectually, and Repetition (Air) Model Assisted by The "Satu Persen" Spotify Podcast on The Speech Writing Skills of Tenth-Grade Senior High School Students - Sharfina Athirah Zahra; Cut Nuraini; Daman Huri (Litteratura: Jurnal Bahasa dan Sastra, 2026)
The ability to write speech texts is one of the essential competencies that students are expected to master in Indonesian language learning.  However, students’ writing skills in this area remain relatively low due to difficulties in developing ideas, organizing the structure of speech texts, and applying appropriate linguistic conventions.  This study aims to examine the effect of the Auditory, Intellectually, and Repetition (AIR) learning model assisted by the Satu Persen Spotify Podcast on the speech-text writing skills of tenth-grade students at SMA Negeri 4 Tambun Selatan.  This research employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design.  The research sample consisted of 42 students in the experimental class and 40 students in the control class, selected through purposive sampling.  The research instrument was a speech-text writing test that had been validated by experts.  Data were analyzed using descriptive and inferential statistics, including the normality test, homogeneity test, paired-samples t-test, independent-samples t-test, and N-Gain analysis with IBM SPSS Statistics 27.  The results indicated that the mean posttest score of the experimental class was higher than that of the control class.  The independent-samples t-test yielded a value of t = –4. 067 with Sig.  (2-tailed) < 0. 001 (p < 0. 05), indicating a statistically significant difference between the experimental and control groups.  Furthermore, the N-Gain analysis showed that the mean improvement in the experimental class was 0. 6525, which was higher than that of the control class (0. 4995).  Based on Hake’s (1999) classification, both groups were categorized as having a moderate level of improvement; however, the experimental class demonstrated greater learning gains.  The mean posttest score of the experimental class was 87. 81, compared to 82. 10 in the control class.  Therefore, it can be concluded that the AIR learning model assisted by the Satu Persen Spotify Podcast has a significant positive effect on the speech-text writing skills of tenth-grade students at SMA Negeri 4 Tambun Selatan.   Keywords: AIR learning model; Spotify podcast; speech-text writing; Indonesian language.